ESTIMATION OF FREEBOARD REQUIREMENTS AGAINST OVERTOPPING OF SURFACE IMPOUNDMENTS UNDER SEISMIC ACTION - Ayoola M.G.; Inyang H.I.; Ogunro V.O. (My University, 2006)
The excitation of structural components and liquid contents of surface impoundments by seismic waves can generate turbulence that is large enough to overtop the bounding berms. In cases in which the liquids are wastes from industrial/municipal operations, their release from impoundments can pose significant risks to the environment. In this analysis, the freeboard magnitudes that can accommodate liquid head levels in impoundments are determined through linkage of configuration of waves in the liquid surface to incident seismic wave characteristics, liquid characteristics and impoundment design. For an impoundment site in a region of ground acceleration levels ranging from 0.2 to 1.0 g and impacted by seismic shear wave velocity of 180 m/s, freeboard requirements are in the range of 0.004–2.0 m on soft soil; 0.008–0.7 m on medium-dense soil; and 0.002–0.1 m for dense soil. For the same impoundment design, ground acceleration and incident wave characteristics, freeboard requirements are directly proportional to the depth of the soil mantle over bedrock. The impoundment slope, which is a key parameter with regards to liquid holding volumetric capacity of the impoundment, is a less significant parameter than depth to bedrock with regard to the size of the required freeboard. This implies that siting of an impoundment should be considered to be critical to impoundment performance in seismic zones.
Keywords: IMPOUNDMENT; WASTE CONTAINMENT; SEISMIC; FREEBOARD; OVERTOPPING